Effect of Suspension Massage Exercise Technique on Cervicogenic Insomnia and Vertebrobasilar Artery Hemodynamics - ZHANG Tianyu; LIU Li; DING Yi; SUN Jie; WANG Shurui; LI Zewen; WANG Jinghua; LI Li (康复学报)
ObjectiveTo investigate the clinical efficacy of suspension massage exercise technique for cervicogenic insomnia and its effect on vertebrobasilar artery hemodynamics.MethodsA total of fifty-six patients with cervicogenic insomnia admitted to the Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine from January 2021 to January 2022 were selected and randomly divided into 28 cases each in observation group and control group using the random number table method. The control group was treated with traditional massage therapy, and the observation group was treated with suspension massage exercise technique, and all the above treatments were 30 min/session, 1 time/day, 5 day/week, for a total of 4 weeks. The clinical efficacy was evaluated by the Pittsburgh Sleep Quality Index (PSQI) scores before and after treatment, and the PSQI and Northwick Park Neck Pain Questionnaire (NPQ) scores were compared before and after treatment. Left vertebral artery (LVA), right vertebral artery (RVA) and basilar artery (BA), and the change of mean blood velocity (Vm) and peak systolic velocity (Vs), and the occurrence of adverse effects during treatment were recorded.ResultsBefore treatment, there were no statistically significant differences in PSQI scores, NPQ scores, Vm and Vs values of LVA, RVA and BA between the two groups (P>0.05). After treatment, total effective rate of the observation group was 82.14%, which was significantly higher than that of the control group (50.00%), and the difference was statistically significant (P<0.05). After treatment, PSQI and NPQ scores were significantly lower in both groups, and the above scores in the observation group were lower than those in the control group, and the differences were statistically significant (P<0.01); after treatment, the scores of each factor of PSQI of the observation group were reduced (P<0.05), and the scores of sleepiness of the control group were reduced (P<0.05). and the scores of sleep quality, sleep disorder, and daytime dysfunction in the control group decreased (P<0.05), and the sleep quality, sleep onset, and sleep duration in the observation group were lower than those in the control group (P<0.05); The Vm values of LVA, RVA and BA increased in both groups after treatment, and the above indexes in the observation group were higher than those in the control group, and the differences were statistically significant (P<0.05). There were no significant adverse reactions during the treatment period in either group.ConclusionSuspension massage exercise technique can effectively improve the sleep quality of patients with cervicogenic insomnia, relieve insomnia symptoms and neck pain, and regulate the hemodynamics of patients' vertebrobasilar artery, which is worthy of clinical promotion and application.